The Exploration of Music Therapy Professional Competency in Chinese Higher Education - Sisi Lin; Lo-Ting Chen (Creative Arts in Education and Therapy)
Competency is the core of vocational and professional training. Under the current situation in the development of music therapy higher education in China, this article analyzes the core characteristics and practical application of the competency-based education (CBE) model and puts forward reflections on the development and implementation of the CBE model in music therapy higher education in China. It is suggested that the music therapy professional competencies in Chinese higher education need multidimensional cooperation and mutual concern among colleges and universities, professional associations, and the job market, and the effect of “professional competencies” on the music therapy profession in China and their contribution to professionalization should be discussed.